(untitled) (Research in Agriculture Livestock and Fisheries, 2019)
The productivity of onion crop is poor due to inappropriate management and agronomic practices in Bangladesh. To figure out the effect of NPK fertilizer rate and spacing on growth parameters of onion a field experiment was conducted. The treatments were consisting of N fertilizer (0, 80,120 and 160 kg/ha), P fertilizer (0, 30, 50 and 70 kg/ha), k fertilizer (0, 50, 75 and 100 kg/ha) and three plant spacing viz., 10 cm × 10 cm, 15 cm × 10 cm and 20 cm × 10 cm. The experiment was designed in RCBD with three replications. Analysis of results indicates that the interaction effect of NPK rate and spacing shows significant (P<0.05) effect on plant height. Highest plant height was obtained in 20 cm × 10 cm spacing and application of 160 kg N/ha, 70 kg P/ha and 100 kg K/ha respectively. Moreover, maximum number of leaves was also found by plants spaced at 10cm and application of highest dose of fertilizers. Lowest plant height and number of leaves was attained in 10 cm × 10 cm spacing and without NPK fertilizer application. The total result analysis reveals that best growth performance of onion was found from 20 cm × 10 cm spacing combined with 160 kg N/ha, 70 kg P/ha and 100 kg K/ha fertilizer amendment. Res. Agric., Livest. Fish.6(1): 19-25, April 2019